Leadership a Critical Text - Simon Western (Sage, 2008)
Leadership: A Critical Text provides a critical review and analysis of the key debates within leadership. Written in an accessible style, this book challenges the notion of the individual or ′hero′ leader. Author Simon Western develops the idea of leadership as a distributed process between lots of agents in an organization. In doing so he provides a new framework which readers can use to understand and implement this ′distributed′ type of leadership.